MISTAGOGI ONLINE SEBAGAI METODE ALTERNATIF KATEKESE DEWASA INI - Dadi, Kanisius Komsiah; Prodeita, Theresia Vita (CREDENDUM: Jurnal Pendidikan Agama, 2019)
Faith education (read: catechesis) today is experiencing various challenges due to the changing times that are increasingly related to technology (digitalization). The catechists are invited to be clever as snakes and sincere like doves (Mat10:16) so that they are still able to instill and proclaim faith along with the demands of the times. Adjustment of methods in the catechesis is an initial step that needs to be implemented so that the proclamation of faith is not dead by digitalization. In addition, the increasing number of Church members needs to be accompanied by adequate assistance from catechists and pastors. This becomes an urgency in proclaiming faith in the midst of the strong flow of information in digital society that can erode faith in Christ. Concern over the problem of strengthening and developing the faith of the people needs to be of particular concern to the Church. The solution that can be offered through this research is the online mistagogical catechesis program as an alternative method to answer challenges and needs in strengthening and proclaiming faith